P568Catheter ablation for atrial fibrillation with heart failure with preserved ejection fraction. (18th June 2020) - Rattka, M; Kuehberger, A; Stephan, T; Weinmann, K; Felbel, D; Baumhardt, M; Bothner, C; Pott, A; Dahme, T
Abstract: Background: Atrial fibrillation (AF) in patients suffering from heart failure with preserved ejection fraction (HFpEF) is associated with increased symptoms and higher morbidity and mortality. Effective treatment strategies for this patient population have not yet been established. Aim: This study aimed to compare the impact of catheter ablation for AF against the current standard therapy on patients with HFpEF. Methods: We retrospectively compared clinical outcomes and echocardiographic parameters of patients with AF and HFpEF, who either underwent medical therapy (rate or rhythm control) or catheter ablation for AF. The primary endpoint was a composite of death and hospitalization for any cause and the secondary endpoint a composite of cardiovascular death and cardiovascular hospitalization. Additionally, we assessed NYHA-class, relevant echocardiographic parameters, current ESC diagnosis criteria for HFpEF at baseline and at the end of follow-up, as well as time-to-AF recurrence in both groups. Resolution of HFpEF was estimated, if both left ventricular mass index(LVMI) and E/e' ratio did not fulfil the ESC-criteria at the end of follow-up. Results: Between January 2013 and December 2018 6.114 patients were treated for AF at our university hospital department. Of those, 752 patients suffered from heart failure symptoms and had echocardiographic diastolic dysfunction. Applying the current ESC-criteria HFpEF was diagnosed in 127 patients. While 59 patients received medical therapy only, catheter ablation for AF was performed in 68 patients. Analysis of AF recurrence in both groups revealed, that in the ablation group 82% of patients and in the medical therapy group only 25% of patients were free from any atrial arrhythmia after one year. Reevaluation of echocardiographic parameters after a mean follow-up period of 39 ± 20 months showed no difference in the medical therapy group, but revealed a significant improvement of the mitral E-wave velocity, E/E' ratio, LVMI, interventricular septal thickness, e' velocity and left ventricular diastolic in the catheter therapy group, suggesting reverse remodeling. Reassessment of criteria for HFpEF diagnosis showed resolution of HFpEF in 35% of invasively treated patients compared to 12% of patients who received conservative therapy only (p = 0.002). Moreover, heart failure symptoms, monitored by NYHA-class, significantly worsened in the medical therapy group, whereas there was significant improvement after catheter ablation. Furthermore, assessment of the primary and secondary endpoint displayed significant lower rates of events. Conclusion: This is the first study comparing the effect of catheter ablation for AF with the current standard therapy in patients with concomitant HFpEF. Our results suggest that catheter ablation is able to induce reverse remodeling of HFpEF, possibly thereby reducing typical heart failure symptoms and hospitalizations.